The Decolonization of the Political Economy of New Media Institutions in Africa: A Case Study on the Pan-African Film Industry - Drew, Sarin Danielle (Centre for Film and Media Studies, 2021)
This study critically analyses an alternative political economy framework to observe the decolonization of new media institutions in Africa. This is because "critically analysing media organisations and media processes in society have come from political economy perspectives." (Jansen, 2003, p. 90). This thesis has a specific focus on the decolonization of the film industry as a case study on new media institutions that are shifting given the fourth industrial revolution. A quantitative methodology was employed to conduct focus groups and interviews with key African film industry actors, this focus group took place at the Durban Film Mart, a Pan-African market for film and television content. The paper critiques the Marxist approach to the political economy of media. This is done to understand the extent that Western political economy frameworks, like Marxism, are relevant in analyzing ownership and media concerning racialized subjects as well as feminist and queer collectives. This paper posits that an Africa, Queer, Muslim, or Feminist political economy framework would explain the relationship between the film industry, industry players, and its audiences better than Marxist assumptions. In this instance, African Feminist, Muslim and Queer approaches to the political economy theory provide a subaltern lens. This study has the intention to investigate new ways in which the decolonization of the political economy of the new Media can create an ideological non-state apparatus or a consciousness industry as denoted by the Frankfurt School. This ideological apparatus would characterize and reflect societal discourses, outside of the nation-state, while creating a sphere for public engagement and deliberation that is equitable and ontologically sound. By ontologically sound, I ask what are the different assumptions about human nature concerning the political economy that can be deduced from a new lens into African media. The answer is that Africa collectives formed outside of class barriers display agency that explains media activity in the twenty-first century. Western ontology and epistemologies assume 4 that colonization robbed Africa of self-determination and agency. This ontological assumption is false. The focus group at the Durban International Film Festival provided the tightest fit to validate my claims that ideologically decolonizing the film industry is garnering public engagement and industry engagement. What are the solutions to the issues of the digital divide and geopolitics of difference that characterise limitations within the burgeoning film industry? This paper investigates to what extent do organic intellectuals, entrepreneurs or youth drive the need for capital and ownership in the industry given that the landscape is shifting. The study found that there is an impetus for decolonizing the industry and that alternative political economy frameworks are more appropriate in analyzing the new media landscape.